2011
DOI: 10.1108/19852511111139804
|View full text |Cite
|
Sign up to set email alerts
|

Network governance in government‐linked companies (GLCs) and non‐government‐linked companies (NGLCs) in Malaysia

Abstract: Purpose -This paper aims to investigate whether or not there exists a relationship between network governance structures in GLCs and NGLCs and performance in Malaysia. In pursuing this objective, the study will explore whether the structures are significantly different and, if so, will seek to establish whether the relationship between their structures and performance of the two groups differs. Design/methodology/approach -The study adopts a matched-pair analysis between GLCs and NGLCs in terms of board listin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…award contracts, strategy, restructuring and financing, acquisitions and divestments etc.) for GLCs either directly or through Government Link Investment Companies (Hamid 2011). …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…award contracts, strategy, restructuring and financing, acquisitions and divestments etc.) for GLCs either directly or through Government Link Investment Companies (Hamid 2011). …”
Section: Literature Reviewmentioning
confidence: 99%
“…To complement the MCCG 2000, the Putrajaya Committee on Government Link Companies (GLC) High Performance (PCG) introduced a framework to guide GLC transformation and upgrade the effectiveness of GLC Boards with the introduction of the 'Green Book'. The study is motivated from the empirical result by Hamid (2011) who concluded that GLCs are relatively more transparent in corporate governance practices and this adds to their higher valuations. Thus, the effectiveness of the audit committee is the main subject in the current study to examine whether the best practice adopted will bring in value to GLCs through its financial reporting quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Jamaludin and Hashim (2017) contended that the company still neglects the significant role of the director's network in the firm. A similar idea was proposed by Hamid (2011) which stated that the need to nominate and retain a member of the board was less concerned with the influence of the networks of the director. Therefore, if the issue remains and no corrective measures have been taken by the firm, it means that this valuable resource was left unused.…”
Section: Directors Network In Technological Innovationmentioning
confidence: 90%
“…Prior research in the field of business and management has extensively applied this theory as a framework for hypothesis testing. Notable examples include studies conducted by Hamid (2011), Stolze et al (2021) and Wadood et al (2022).…”
Section: Theories Literature Review and Hypotheses Development 21 The...mentioning
confidence: 99%